“The Humble Cosmopolitan: Rights, Diversity, and Trans-State Democracy” by Luis Cabrera (Glocalism: Journal of Culture, Politics and Innovation, 2020)
It is often alleged that debates on cosmopolitanism and global justice are blind towards non-western normative resources. In The Humble Cosmopolitan: Rights, Diversity, and Trans-state Democracy, published by the Oxford University Press in 2020, Luis Cabrera responds to such a charge by presenting an account of institutional cosmopolitanism imbued with the norm of political humility. By interpreting Bhimrao Ramji Ambedkar’s political vision and the practices inspired by it, Cabrera articulates a theory of institutional cosmopolitanism that not only has an egalitarian slant, but more importantly is imbued with the ideal of political humility.
Keywords: Luis Cabrera; The Humble Cosmopolitan; Bhimrao Ramji Ambedkar; institutional cosmopolitanism; political humility